Organizational Commitment Reviewed from Work-Life Balance in Students Who Study While Working - Magdalena, Elfrida; Muharsih, Lania; Hakim, Arif Rahman (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Human potential that can be developed can increase productivity and employee performance. The amount of commitment to a company influences the success of an employee's performance. Some of the phenomena found in employees who study at Buana Perjuangan University, Karawang, are the difficulty of managing their schedule between study and work, physical fatigue, and having to hide their identity as a student at their place of work. This research examines how much influence work-life balance has on organizational commitment among Buana Perjuangan University Karawang students who study while working. Participants in this research were 319 students studying while working. The research instrument used was the organizational commitment scale consisting of 24 items as the dependent variable and the work-life balance scale consisting of 17 items as the independent variable. The sampling technique used was quota sampling. The data analysis technique in this research uses simple linear regression analysis with the help of the SPSS statistics 25 program. Based on the results of the hypothesis test, a significance value of 0.004 <0.05 is obtained, which means work-life balance has a positive influence on organizational commitment, with an R square value of 0.708, which means that the influence contributed by the work-life balance variable on organizational commitment is 70.8% and the remaining 29.2% is influenced by other variables. This means that there is a relationship between the work-life balance variable and organizational commitment. The higher the work-life balance, the higher the level of commitment to the organization.Potensi manusia yang dapat dikembangkan mampu meningkatkan hasil keproduktifan juga kinerja karyawan. Besar komitmen terhadap sebuah perusahaan mempengaruhi keberhasilan kinerja seorang karyawan. Beberapa fenomena yang terdapat pada karyawan yang kuliah di Universitas Buana Perjuangan Karawang yaitu sulitnya mengatur jadwal antara kuliah dan bekerja, kelelahan fisik, serta harus menyembunyikan identitasnya sebagai mahasiswa di tempatnya bekerja. Penelitian ini menguji seberapa besar pengaruh work-life balance terhadap komitmen organisasi pada mahasiswa Universitas Buana Perjuangan Karawang yang kuliah sambil bekerja. Partisipan dalam penelitian ini adalah mahasiswa yang kuliah sambil bekerja berjumlah 319 orang. Instrumen penelitian yang digunakan adalah skala komitmen organisasi yang terdiri dari 24 aitem sebagai variabel dependen dan skala work-life balance yang terdiri dari 17 aitem sebagai variabel independen. Teknik pengambilan sampel yang digunakan adalah quota sampling. Teknik analisis data dalam penelitian ini menggunakan analisis regresi linear sederhana dengan bantuan program SPSS statistic 25. Berdasarkan hasil uji hipotesis didapatkan nilai signifikansi sebesar 0,004 < 0,05 yang berarti work-life balance memiliki pengaruh yang positif terhadap komitmen organisasi, dengan nilai R square sebesar 0.708 yang berarti pengaruh yang disumbangkan variabel work-life balance terhadap komitmen organisasi sebesar 70,8% dan sisanya sebesar 29.2% dipengaruhi oleh variabel-variabel lain. Artinya terdapat hubungan antara variabel work-life balance dan komitmen organisasi. Semakin tinggi work-life balance maka semakin tinggi tingkat komitmen terhadap organisasi.